Hadith #3682 - Sunan Abi Dawud - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Dylm al-Hmyry ديلم الحميري ويقال هو فيروز الديلمي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Ibn Ishaq محمد بن إسحاق بن يسار‎; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was asked about bit’. He replied: Every liquor which intoxicates is forbidden. Abu Dawud said: I read out this tradition to Yazid bin ‘Abd Rabbihi al-Jurjisi. Muhammad bin Hard told you this tradition from al-Zabidi from al-Zuhri through his chain of narrators. This version added: Bit’ is the nabidh from honey, which the people of the Yemen would drink. Abu Dawud said: I heard Ahmad bin Hanbal say: There is no god but Allah. there was none stronger in memory an
Grade: Sahih